2020
DOI: 10.1177/0049475520911233
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and stroke disease risk among doctors: a cross-sectional study

Abstract: The leading causes of death in the world are cardiovascular disease (CVD) and stroke according to the World Health Organization, as is also the case in India. There is also a high prevalence of major conventional risk factors in India, where 18.3%, 9.0% and 14.1% of adults are diagnosed with hypertension, diabetes and smoking, respectively. The aim of the present study was to look at the risk of CVD among doctors in our country using a validated tool developed by the National Health Service (NHS) in the UK, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
2
4
1
Order By: Relevance
“…5,14,18 Others additionally found overweight/ obesity, metabolic syndrome, and a family history of CAD as the most predominant risk factors for CVDs among the physicians. 6,14,15,18 The contradictory findings in our study were the significant association of CAD among the physicians with weekly work < 55 h and exercise ≥ 3 days/ week from univariate analysis. Unfortunately, data on the duration of these practices were not available to explore the cause and effect.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…5,14,18 Others additionally found overweight/ obesity, metabolic syndrome, and a family history of CAD as the most predominant risk factors for CVDs among the physicians. 6,14,15,18 The contradictory findings in our study were the significant association of CAD among the physicians with weekly work < 55 h and exercise ≥ 3 days/ week from univariate analysis. Unfortunately, data on the duration of these practices were not available to explore the cause and effect.…”
Section: Discussioncontrasting
confidence: 74%
“…Only older age, male gender, and moderate/ severe CAC score were found to be independent risk for CAD. Some of these risk features of CAD were also identified in previous studies reporting risk of CVDs among health professionals 5,6,13–16 especially physicians who were found to have higher risk than nurses. 5…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…[ 19 ] Cardiovascular events at a younger age is one of the major contributors of mortality among doctors in India. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported a higher risk of CVD among physicians. [18][19][20] This can attribute to occupation-related stress, poor lifestyle and habits, and lack of exercise leading to high blood pressure (BP) and obesity, consequent to CVD. 19,20 Our hospital conducted the corporate social responsibility (CSR) project, "Save Doctors' Heart", to assess the cardiac health of Thai physicians, specifically CAD through cardiac tests.…”
Section: Introductionmentioning
confidence: 99%